2021
DOI: 10.5194/bg-18-2609-2021
|View full text |Cite
|
Sign up to set email alerts
|

The role of termite CH<sub>4</sub> emissions on the ecosystem scale: a case study in the Amazon rainforest

Abstract: Abstract. The magnitude of termite methane (CH4) emissions is still an uncertain part of the global CH4 budget and current emission estimates are based on limited field studies. We present in situ CH4 emission measurements of termite mounds and termite mound subsamples performed in the Amazon rainforest. Emissions from five termite mounds of the species Neocapritermes brasiliensis were measured by use of a large flux chamber connected to a portable gas analyser measuring CH4 and CO2. In addition, the emissions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 81 publications
2
10
1
Order By: Relevance
“…However, considering the high variation associated with the fluxes, it seems obvious that if the sizes of the studied mounds are too close to each other, the relationships between mound volume and gas fluxes are difficult to detect. In this study, the mound volumes ranged from 0.023 to 0.259 m 3 (Table 1) including notably more size variance than the earlier comparable studies (0.02 to 0.077 m 3 ) (Jamali et al, 2013;van Asperen et al, 2021). We found that the measured CO2 fluxes were linearly correlated with the termite mound volume during the wet season (Fig.…”
Section: Soil Co2 and Ch4 Fluxes Around Termite Moundssupporting
confidence: 58%
See 2 more Smart Citations
“…However, considering the high variation associated with the fluxes, it seems obvious that if the sizes of the studied mounds are too close to each other, the relationships between mound volume and gas fluxes are difficult to detect. In this study, the mound volumes ranged from 0.023 to 0.259 m 3 (Table 1) including notably more size variance than the earlier comparable studies (0.02 to 0.077 m 3 ) (Jamali et al, 2013;van Asperen et al, 2021). We found that the measured CO2 fluxes were linearly correlated with the termite mound volume during the wet season (Fig.…”
Section: Soil Co2 and Ch4 Fluxes Around Termite Moundssupporting
confidence: 58%
“…7). Methane fluxes ranged from 0.02 to 3.66 mg CH4-C m -2 h -1 and were 2-20 times lower than those reported in earlier studies (0.4-6 mg CH4-C m -2 h -1 , van Asperen et al, 2021;Jamali et al, 2013). As in earlier chamber measurement studies termites have been other than fungus-growing species, this result was expected: in fungus-growing termites a large proportion of the mound total CO2 fluxes originate from aerobic fungus gardens which seem not to emit measurable amounts of CH4 (Darlington et al, 1997).…”
Section: Soil Co2 and Ch4 Fluxes Around Termite Moundsmentioning
confidence: 51%
See 1 more Smart Citation
“…The accumulation of dead wood from tree mortality can further destabilize the C cycle by increasing forest vulnerability to fire, if these areas are near human-ignition sources.Drought-induced stress from water limitation in terra firme forests can reduce the overall capacity of the forest system to uptake atmospheric CO2 and increase tree mortality in old growth Amazonian forests(Phillips et al 2010, van der Molen et al 2011) (see Section 23.1.3 in Chapter 23). Drought can directly reduce the photosynthetic capacity of forests by promoting stomatal closure) that suggests forest vulnerability to drought is heterogeneous across the Amazon, depending on forest species composition, functional traits, and local environments(Cosme et al 2017, Esquivel- Muelbert et al 2020.…”
mentioning
confidence: 99%
“…Upland tree stems and leaf surfaces were suggested as potential sinks (Covey & Megonigal, 2019), yet there are no direct observations of such mechanism. Within the canopy, bromeliads (Martinson et al, 2010) and mounds of soil feeding termites (van Asperen et al, 2021) were found to be large site-specific CH 4 hotspots. The large heterogeneity of the latter sources makes it difficult to upscale them and a potential underestimation of these sources at the ecosystem scale seems likely (SPA, 2021).…”
Section: Introduction 121 Methane In the Amazon Carbon Cyclementioning
confidence: 98%